2008
DOI: 10.4049/jimmunol.180.6.3757
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Does Not Affect IEL Development in the Thymus but Regulates Homeostasis of Putative Precursors and Mature CD8αα+ IELs in the Intestine

Abstract: Mice devoid of the IL-15 system lose over 90% of CD8αα+ TCRαβ and TCRγδ intestinal intraepithelial lymphocytes (iIELs). Previous work revealed that IL-15Rα and IL-15 expressed by parenchymal cells, but not by bone marrow-derived cells, are required for normal CD8αα+ iIEL homeostasis. However, it remains unclear when and how the IL-15 system affects CD8αα+ iIELs through their development. This study found that IL-15Rα is dispensable for the thymic stage of CD8αα+ TCRαβ and TCRγδ iIEL development but is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…IL-15 is a critical cytokine for the development of IELs 13,18,19 . Previous studies indicated that treatment of CD4 À CD8 À TCRb þ NK1.1 À B220 À CD5 þ cells with IL-15 increased the expression of CD8aa 19,20 . Consistent with these previous reports, IL-15-mediated stimulation of CD4 À CD8 À TCRb þ NK1.1 À B220 À CD5 þ cells from control mice increased the expression of CD8aa (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-15 is a critical cytokine for the development of IELs 13,18,19 . Previous studies indicated that treatment of CD4 À CD8 À TCRb þ NK1.1 À B220 À CD5 þ cells with IL-15 increased the expression of CD8aa 19,20 . Consistent with these previous reports, IL-15-mediated stimulation of CD4 À CD8 À TCRb þ NK1.1 À B220 À CD5 þ cells from control mice increased the expression of CD8aa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IL-15 is critical for the development of TCRab þ CD8aa þ IELs 18,19 . The role of IL-15 in the development of TCRab þ CD8aa þ IELs was suggested by the observation that IL-15 could support the expression of CD8a by the precursors of TCRab þ CD8aa þ IELs in vitro 19,20,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancers neighboring several genes in GO categories involved in leukocyte and lymphocyte activation and cytokine interactions also exhibited significant increases in accessibility with colonization in TCR γδ + IELs (Dataset S10D); these genes include Cd28, Cxcr4, Il15ra, Il2, Il10, Cd40lg, and Ccr7, some of which are associated with the activation of T cells and have been implicated in shaping the IEL compartment. As noted above, IL-15 responsiveness has been shown to be key for the accumulation of CD8αα + TCRβ + cells and also for TCR γδ + cells (25)(26)(27)(28).…”
Section: Significancementioning
confidence: 99%
“…These include ahr, encoding the aryl hydrocarbon receptor (AhR), which controls accumulation of CD8αα + TCRβ + IELs (23); id2, which is required for accumulation of CD8αβ + IELs (24); il15ra (IL15 receptor α), which encodes a component of the IL-15 receptor; and il7r, which specifies a component of the IL-7 receptor. IL-15 and IL-7 are important cytokines controlling the accumulation and function of CD8αα + IELs (25)(26)(27)(28). Additionally, members of two pathways, KEGG "Cell adhesion molecules" (35 genes) and KEGG "ECM-receptor interaction" (25 genes), were also associated with enhancers exhibiting increased accessibility in CONV-R compared to GF TCR αβ + IELs (Dataset S10A); changes in chromatin state affecting enhancers positioned next to genes in these pathways may reflect broad changes in TCR αβ + interactions with the intestinal epithelium upon colonization.…”
Section: Significancementioning
confidence: 99%